Validation of temperature‐controlled rheo‐MRI measurements in a submillimeter‐gap Couette geometry. (7th April 2021) - Milc, Klaudia W.; Serial, Maria R.; Philippi, John; Dijksman, Joshua A.; van Duynhoven, John P. M.; Terenzi, Camilla
Abstract: A temperature‐controlled submillimeter‐gap (500 μm) rheo‐magnetic resonance imaging (MRI) Couette cell has been developed to measure confined flow of soft structured materials under controlled temperature. The proposed setup enables performing rheo‐MRI measurements using (i) a spatially uniform temperature control over the range 15°C to 40°C and (ii) a high spatial resolution up to 10 μm, as a consequence of the improved mechanical stability of the in‐house developed rotating elements. Here, we demonstrate the performance of the cell for the rheo‐MRI velocimetry study of a thixotropic fat crystal dispersion, a complex fluid commonly used in food manufacturing. The submillimeter‐gap geometry and variable temperature capability of the cell enable observing the effects of shear‐ and temperature‐induced fat recrystallization on both wall slip and shear banding under strongly confined flow. Our improved rheo‐MRI setup opens new perspectives for the fundamental study of strongly confined flow, cooperative effects, and the underlying interparticle interactions and for ultimately aiding optimization of products involved in spreading/extrusion, such as cosmetics and foods. Abstract : A 500‐μm‐gap Couette cell with temperature control for rheo‐MRI measurements was implemented and validated. The cell enables reliable submillimeter velocimetry rheo‐MRI studies thanks to the improved stability of the rotating inner cylinder by a factor of ~10 as compared with the currently available rheo‐MRI geometries. The validated uniform temperature control extends the application of the cell to variable temperature studies.